Piezo1-mediated mechanotransduction regulates the translational activity, function and lung pathogenicity of group 2 innate lymphoid cells - MinYeong Lim; Seonjun Park; Yoon Ha Joo; Sung Eun Kim; Min Hee Ham; TaeSoo Kim; Kihyuck Kwak; Sung Joon Kim; Jung Chan Lee; Sung Ho Park; Hye Young Kim (Signal Transduction and Targeted Therapy)
Abstract Group 2 innate lymphoid cells (ILC2s) are central effectors of type 2 immune responses in the lung; however, how mechanical cues regulate their function remains unclear. Here, we identified the mechanosensitive ion channel Piezo1 as a key regulator of ILC2 effector function through translational control. Piezo1 is highly expressed in murine and human ILC2s, and its activation by mechanical stress or the Piezo1 agonist, Yoda1 induces calcium influx, triggering mTOR signaling and selectively enhancing IL-13 protein production. Conditional deletion of Piezo1 in ILC2s reduced mTOR activation and puromycin incorporation, leading to impaired protein synthesis and attenuated lung inflammation and fibrosis in the IL-33, Alternaria alternata, and bleomycin models. scRNA-seq and scATAC-seq confirmed that Piezo1-deficient ILC2s retained Il13 transcription and chromatin accessibility but presented translational suppression, as evidenced by protein‒mRNA interactions. Pharmacologic mTOR inhibition phenocopied Piezo1 loss, supporting the functional relevance of the Piezo1–mTOR axis. These findings demonstrate that Piezo1 functions as a mechanosensor that integrates biomechanical cues to regulate cytokine output via mTOR-mediated translation. Targeting Piezo1 signaling or its downstream effectors may provide therapeutic benefits in type 2 inflammation–associated lung diseases.